Emerging approaches for industrial sustainability and feasible applications in India. (2017) - Shankar, Y. Shiva; Mohan, Devendra; Vaid, Paras; Anand, Mohit; Ganesh, Shashank
Over the past few decades, emerging economies like India have seen unprecedented growth in industrialisation. Improper planning has resulted in pollution and environmental risks due to excessive consumption of natural resources. For a developing country like India, establishment of industrial clusters on the concepts of industrial symbiosis has enormous potential to curtail resource utilisation and environmental degradation. As in case of nature, there is continuous flow of materials and energy through various levels, industrial ecology also involves somewhat similar approach involving exchanges of materials and energy at different levels amongst participating industries. The paper discusses about the emerging approaches to achieve industrial sustainability that can be applied to industrial sectors such as thermal power plant (TPP), sugar and cement production industries. The paper will also discuss about the complexities involved and the considerations required, while planning the development of such industrial complexes in Indian scenario.